Perlindungan Hukum Atas Informasi Bisnis Dalam Perjanjian Kerja di Kabupaten Polewali Mandar - Rini Apriani Anwar; Erlina (Alauddin Law Development Journal (ALDEV), 2022)
The main problem of this research is how the form of legal protection for business information on the Mother of Embroidery in Polewali Mandar Regency as well the form of dispute resolution for the violation of business information in the work agreement for Mother Embroidery in Polewali Mandar Regency. This research uses a type of field research, this type of research uses qualitative research with the research approach used is normative and sociological. As for the source of this research is the owner of Mother Embroidery herself. Then the data collection mothods used are interviews, documentation and library research. While data management techniques are in the form of editing and verification as well as data analysis with data reduction, data presentation, and conclusion reasoning. The result of this study indicate that the leakage of business information regarding Mother Embroidery in polewali Mandar Regency, in this case there is a work agreement violation that violates the rules of Article 1320 of the Civil Code then the form of dispute resolution against business information violations carried out outside the court is also called Alternative Dispute Resolution (ADR) in the work agreement for the Mother of Embroidery in Polewali Mandar Regency through mediation. The implication in this research is that before hiring employees or other parties, try to provide a good understanding, explain in detail the form of work agreement for workers that will be accepted as well as the initiative from the business owner to cooperate with local officials regarding socializing to the community regarding the steps of workers so that this does not occur problem or conflict.